The Codes of the Street in Risky Neighborhoods : A Cross-Cultural Comparison of Youth Violence in Germany, Pakistan, and South Africa /: A Cross-Cultural Comparison of Youth Violence in Germany, Pakistan, and South Africa. ([2019]) - Heitmeyer, Wilhelm; Howell, Simon; Kurtenbach, Sebastian; Rauf, Abdul; Zamān, Muḥammad; Zdun, Steffen
No abstract available